2016
DOI: 10.5830/cvja-2015-087
|View full text |Cite
|
Sign up to set email alerts
|

Assessing perinatal depression as an indicator of risk for pregnancy-associated cardiovascular disease

Abstract: Cardiovascular conditions associated with pregnancy are serious complications. In general, depression is a well-known risk indicator for cardiovascular disease (CVD). Mental distress and depression are associated with physiological responses such as inflammation and oxidative stress. Both inflammation and oxidative stress have been implicated in the pathophysiology of CVDs associated with pregnancy. This article discusses whether depression could represent a risk indicator for CVDs in pregnancy, in particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…There is, however, a paucity of data on the involvement of O & NS processes in perinatal depression. There is one paper hypothesizing that increased oxidative stress in perinatal depression could contribute to cardiovascular pathology in women with pre-eclampsia (Nicholson et al, 2016). Nevertheless, elevated O & NS in pregnancy may have detrimental effects by increasing the risk towards perinatal depression and physio-somatic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a paucity of data on the involvement of O & NS processes in perinatal depression. There is one paper hypothesizing that increased oxidative stress in perinatal depression could contribute to cardiovascular pathology in women with pre-eclampsia (Nicholson et al, 2016). Nevertheless, elevated O & NS in pregnancy may have detrimental effects by increasing the risk towards perinatal depression and physio-somatic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…No previous studies have investigated oxidative stress in perinatal depression. Nevertheless, a hypothesis had been proposed describing a possible relationship between perinatal depression, oxidative stress, and risk for pregnancy-associated cardiovascular diseases (CVD) (Nicholson et al 2016). An animal study showed an association of lowered maternal care, a possible indicator of maternal emotional problems, and increased oxidative stress in the brain of nursing mothers (Nicholson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a hypothesis had been proposed describing a possible relationship between perinatal depression, oxidative stress, and risk for pregnancy-associated cardiovascular diseases (CVD) (Nicholson et al 2016). An animal study showed an association of lowered maternal care, a possible indicator of maternal emotional problems, and increased oxidative stress in the brain of nursing mothers (Nicholson et al 2016). It is not unlikely that lowered IgM-mediated regulatory responses during pregnancy may play a role in the increased incidence of cardiovascular complications during pregnancy and in women of childbearing age (Mohamed 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal depression may contribute to increased CVD risk in women through inflammatory changes that promote hypertension in the form of preeclampsia and the development of gestational diabetes, but this has yet to be directly tested. 143,144 The following two sections will summarize the recent advances in the literature pertaining to depression and CVD risk in gestational diabetes and preeclampsia.…”
Section: Perinatal Depressionmentioning
confidence: 99%